GAMIFICATION IN ESL/EFL TEACHING: CONCEPTUAL VIEWS, BENEFITS AND CHALLENGES - Ishankhudjaeva Feruza Abduboriyevna (Bright Mind Publishing, 2026)
Gamification has emerged as an innovative pedagogical approach in English as a Second Language (ESL) and English as a Foreign Language (EFL) education, integrating game design elements to enhance learner engagement, motivation, and language retention. This article is discussed about gamification in teaching.
Keywords: Gamification, education, student, teaching, SLA, learner, feedback